The Older, the Wiser? Investigating the Effect of CEO Age on the Bank Performance in Malaysia - Chua, Mei-Shan; Roslen, Siti Nurhidayah; Mary, Pang (Information Management and Business Review, 2023)
This paper aims to investigate the impact of CEO age on commercial bank performance in Malaysia. Our sample data consists of 84 observations from commercial banks in Malaysia from 2016 to 2021. Using the Quantile Regression Method, we find that the CEO’s Age positively influences the commercial bank’s performance. This finding indicates the wisdom of the CEO in making decisions when they are getting older, positively affecting the commercial bank’s performance. The result is consistent with the resource-based view; the CEO is the invaluable human capital providing experience in managing the bank’s performance. Our findings guide practitioners in hiring a qualified CEO